Systematic Surveillance of an Emerging Picornavirus among Cattle and Sheep in China - Chengyuan Ji; Yao Zhang; Yiqiu Feng; Xinqin Zhang; Jiale Ma; Zihao Pan; Atsushi Kawaguchi; Huochun Yao (Microbiology Spectrum, 2023)
ABSTRACT Emerging viruses are a constant threat to human and animal health. Boosepivirus is a novel picornavirus considered a gastrointestinal pathogen and has broken out in recent years. In 2020, we identified a strain of boosepivirus NX20-1 from Chinese calf feces and performed genetic characterization and evolutionary analysis. NX20-1 was closely related to the Japanese strain Bo-12-38/2009/JPN and belonged to Boosepivirus B. We found that 64 of 603 samples (10.6%) from 20 different provinces across the country were positive for boosepivirus by reverse transcription (RT)-PCR. Further, coinfection with other diarrheal pathogens was also present in 35 of these positive samples. Importantly, we found the prevalence of boosepivirus in sheep as well, indicating that Boosepivirus can infect different domestic animals. Our data suggest that boosepivirus is a potential diarrheal pathogen, but the pathogenicity and the mechanism of pathogenesis need further study. IMPORTANCE We identified a novel picornavirus, boosepivirus, for the first time in China. Genetic evolutionary analysis revealed that NX20-1 strain was closely related to the Japanese strain Bo-12-38/2009/JPN and belonged to Boosepivirus B. In addition, we found that the virus was prevalent in China with an overall positivity rate of 10.6% (64 of 603 samples), and there was significant coinfection with other pathogens. Importantly, we found the prevalence of boosepivirus in sheep as well, suggesting that boosepivirus has a risk of spillover and can be transmitted across species.